Kesejahteraan Psikologis Pada Siswa: Tinjauan Literatur Terhadap Faktor Penyebab - Madya Bangsa Opsiviantoto; IGAA Noviekayati (CV. ITTC INDONESIA, 2026)
Psychological well-being is a positive mental condition that enables individuals to develop their potential, live meaningfully, and cope with life's challenges and pressures. For students, psychological well-being plays a crucial role in supporting academic success, emotional resilience, and overall educational experiences. This study aims to identify and map the various causal factors influencing students' psychological well-being through a systematic literature review approach. The literature search was conducted using the PICOC framework via Google Scholar with the assistance of Publish or Perish, Zotero, and Covidence applications. Of the 100 articles identified, 18 met the inclusion criteria and were analyzed using a thematic approach. The results indicate that factors influencing students' psychological well-being can be grouped into four main categories: individual factors (emotional intelligence, self-efficacy, resilience, and motivation), family factors (parenting styles and family support), school/academic factors (school climate, school connectedness, academic stress, and teacher support), and social factors (peer social support and social media). These findings confirm that students' psychological well-being is formed through complex interactions between individual characteristics, family environment, school environment, and broader social contexts.